(untitled) (Medical Forum Monthly, 2024)
Every individual, collective political will, every institution, role of a female, civil society and media are required to create clean and healthy drug free atmosphere in Lahore. This was stated by Federal Secretary Anti Narcotics Control Chaudhry Iftikhar Ahmad during a seminar. The seminar titled “Free Drug Lahore, How and Why” was held at a hotel by Mir Khalil-ur-Rehman Memorial Society (MKRMS) with the collaboration of the Ministry of Narcotics Control and Anti Narcotics Force. Speakers from various walks of life spoke on the occasion and highlighted the causes of effects of drugs and preventive measures to stop their spread. They all agreed that the education, awareness, planning, treatment, political and civil society can help make Lahore a drug free city. Chaudhry Iftikhar, who was the chief guest on the occasion said that this was the time when everyone would not only have to come forward but share his or her commitment and cooperation to make the project successful. He urged the leadership of all political parties to add drug free project into their manifestos. He said that as family was a key component of a social mobilization, it should play its part to create a drug free atmosphere in the city and added that without the participation of NGOs, Civil Society and the Media, the goal could not be achieved.